2013
DOI: 10.1371/journal.pone.0077224
|View full text |Cite
|
Sign up to set email alerts
|

Alternative 5’ Untranslated Regions Are Involved in Expression Regulation of Human Heme Oxygenase-1

Abstract: The single nucleotide polymorphism rs2071746 and a (GT)n microsatellite within the human gene encoding heme oxygenase-1 (HMOX1) are associated with incidence or outcome in a variety of diseases. Most of these associations involve either release of heme or oxidative stress. Both polymorphisms are localized in the promoter region, but previously reported correlations with heme oxygenase-1 expression remain not coherent. This ambiguity suggests a more complex organization of the 5’ gene region which we sought to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 31 publications
1
54
0
Order By: Relevance
“…The 5′RACE results demonstrated the presence of CYP6AY1 alternative splice products in the 5′-UTR. Studies on human surfactant protein (SFTPA1/2) and heme oxygenase-1 have demonstrated that alternative splicing of the 5′-UTR can impact mRNA stability and translation efficiency (Wang et al, 2005;Kramer et al, 2013). In addition, at least five alternative splicings in the 5′-UTR of the P450 gene CYP19B1 have been found in rainbow trout, which may be involved in the developmental regulation of this gene or to the control of distinct gonadal cell types (von Schalburg et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The 5′RACE results demonstrated the presence of CYP6AY1 alternative splice products in the 5′-UTR. Studies on human surfactant protein (SFTPA1/2) and heme oxygenase-1 have demonstrated that alternative splicing of the 5′-UTR can impact mRNA stability and translation efficiency (Wang et al, 2005;Kramer et al, 2013). In addition, at least five alternative splicings in the 5′-UTR of the P450 gene CYP19B1 have been found in rainbow trout, which may be involved in the developmental regulation of this gene or to the control of distinct gonadal cell types (von Schalburg et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…151 Microsatellite polymorphisms can affect alternative splicing in the HMOX1 5′ untranslated region, thus providing an additional regulatory mechanism for HMOX1 translation. 152 Additional SNPs in HMOX1 have been identified, including rs2071746 T/A which has been associated with increased risk of Parkinson’s disease, and with protection from cardiovascular disease. 153154 …”
Section: Regulation Of Heme Oxygenase Gene Expressionmentioning
confidence: 99%
“…The hypermutable nature of STRs and their large unascertained reservoir of functionality make them an ideal source of evolutionary adaptation, speciation, and disease (Hannan et al 2018;Bagshaw et al 2017;Press et al 2017;Ohadi et al2015;Valipour et al 2013;Heidari et al 2012). In line with the above, recent reports indicate a role of repetitive sequences in the creation of new transcription start sites (TSSs) in human (Nazaripanah et al 2018;Alizadeh et al 2018;Kramer et al 2013).…”
Section: Introductionmentioning
confidence: 74%